Design and Fabrication of Gasification Combined Cycle in Power Plant - Rejus Kumar, Arun V; Francis Britto, A. Sagai (International Journal of Psychosocial Rehabilitation, 2019)
These days, the major source of electricity in our country is produced from thermal power, i.e., coal. The vast resources of coal we have are not of high carbon content. The form of coal primarily mined in India is lignite, which has less carbon content. We are not being able to maximize the output from the power plants using these coals only because of the inferior quality of coal. As a result, there is much wastage of these valuable resources.